Let's Get Healthy - Allensworth, Ashlee (My University, 2022)
Obesity is a prevalent disease and of growing concern. Preventative medicine by weight loss can help in the improvement of body mass index (BMI), weight, lipid (total cholesterol), and A1c levels. This paper discusses the implementation of a 12-week weight-loss program in a primary care office setting for participants agreeing to take part in the program. The weight-loss program provided an educational toolkit, daily tracking logs, measurements of their BMI, weight, lipid (total cholesterol), and A1c levels, and monthly “check-in” appointments. Education core components included a 1600 calorie diet, five days per week of at least 30 minutes of a cardio-type activity, a minimum of at least eight hours of sleep per night, consumption of least six 8 oz. glasses of water, and use of a GLP-1 agonist (Wegovy) if not contraindicated. Daily tracking logs were reviewed with the participants at one- and two-month intervals to evaluate the participants’ progress. All 30 participants who completed had an improvement in their BMI, weight, lipid (total cholesterol), and A1c levels.
Keywords: weight loss, weight-loss program, lipids, A1c, GLP-1 agonist, sleep health, 1600 calorie diet